Issues to assume in the tertiary education - Trujillo Colorado, Isabel Cristina
The following article analyses the World Bank´s recommendations and the media publications carried out about the tertiary education implementation from the economical apparatus perspective to minimise the inequality and inequity gaps, the universities concerns about the tertiary education issue addressed in the Development Plan 2015 - 2018 and the vice minister of education explanations about this matter; strengthen the articulation with the technical middle and the involvement of the productive sector for the working placement.